Riding the Wave : applying project management science in the field of emergency management - Boyarsky, Andrew (Boca Raton: CRC Press, Taylor & Francis, 2024)
"Emergency managers and public safety professionals are more frequently being called on to address increasingly more challenging and complex critical incidents, with a wider variety and intensity of hazards, threats, and community vulnerabilities. Much of the work that falls into the scope of emergency managers- prevention, preparedness, mitigation- is "blue sky planning" and can be contained and effectively managed within projects. This book provides a foundational project management methodology relevant to the emergency management practice, and explains and demonstrates how project management can be applied in the context of emergency and public safety organizations. This book is intended for emergency managers and public safety professionals who are responsible for developing emergency programs and plans, including training courses, job aids, computer applications and new technology, developing exercises, and for implementing these plans and components in response to an emergency event. This audience includes managers in emergency and first response functions such as fire protection, law enforcement and public safety, emergency medical services, public health and healthcare, sanitation, public works, business continuity managers, crisis managers, and all managers in emergency support functions as described by FEMA. This would include those who have responsibility for emergency management functions, even without the related title"
The Accidental Project Manager -- Why is Project Management a Good Fit for Emergency Management -- Risk Management for Emergency Management and Public Safety -- Developing Strategies and Capabilities to Manage Major Risk Events -- Developing the Project Scope -- Developing the Schedule -- Developing the Project Budget -- Developing the Human Resources Plan -- Developing the Quality Plan -- Developing the Risk Plan -- Developing the Stakeholder and Communications Plan -- Procurement, Contract Management and Reporting -- Monitoring and Control: Tracking Project Progress -- Program Management and Project Portfolio Management -- Emergency Response as a Project -- Quality Management in Emergency Management Programs and Continuous Improvement for Responses, Projects and Programs -- Project Leadership.
Keywords: Emergency management; Public safety